On groups whose subgroups of infinite special rank are transitively normal - Semko, N.N.; Velychko, T.V. (Algebra and Discrete Mathematics, 2017)
This paper sheds a light on periodic soluble groups whose subgroups of infinite special rank are transitively normal.